APPLICATION OF MULTICRITERIAL OPTIMIZATION IN MODELING OF THE SIGNAL RECOVERY PROCESS DIFFERENTIAL TRANSFORMATIONS - Zasyadko , A. A. (Problems of Informatization and Control, 2021)
In this paper, the inaccurately defined systems of linear algebraic equations, to which the differential model of the signal recovery problem is reduced, are proposed to be solved with the help of multicriteria optimization. Partial criteria for stability and accuracy form a multi-criteria objective function, which is a nonlinear scheme of trade-offs. The resulting solution is optimal.